Fertility after treatment of a noncommunicating rudimentary horn pregnancy: A case report - Salina Zhang; Alessandra Lamari; Edward Ferris; Priya Maseelall (Elsevier, 2022)
Rudimentary horn pregnancies are rare but are associated with high mortality and morbidity. The diagnosis can be difficult as it may be challenging to distinguish a rudimentary horn pregnancy from an intrauterine pregnancy on ultrasound. Magnetic resonance imaging can often be used to confirm a rudimentary horn pregnancy. When a second-trimester rudimentary horn pregnancy is diagnosed, surgical intervention should be performed to avoid uterine rupture and hemoperitoneum. The correct diagnosis and management of rudimentary horn pregnancies help to preserve the fertility of younger patients.This case report describes a second-trimester rudimentary horn pregnancy that was diagnosed by ultrasound and magnetic resonance imaging. It was then surgically resected via laparotomy. This patient maintained her fertility and was able to conceive naturally, leading to an uncomplicated term pregnancy.